DEVELOPING VISUAL ART IN LEARNING SPEAKING SKILL FOR STUDENTS OF JUNIOR HIGH SCHOOL - Betty Simanjuntak; Amrin Saragih; Willem Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2018)
The objective of this study was to develop English learning media based on students’ needs. This research was conducted in SMP N 37 Medan for students in grade VII which consists of 30 students. This study followed the steps of research and development proposed by Borg and Gall (1983), which are 1) need analysis; 2) planning (develop preliminary form of product); 3) Collecting data; 4) designing media; 4) media evaluation; 5) revising (designing final product). It was found that 96.66% students agreed that the existing an interactive learning medium currently used by the students of Junior High School. The more relevant media were developed based on student needs, which can provide opportunities for students to participate in the classroom. The learning media were developed into 4 media based on 4 units of speaking materials. Then the learning media were validated by two experts. The average score of the validation was 90. It showed that the developed learning media were very good, relevant and feasible.Keywords:       English learning media, speaking, visual art media.